Jhon Fiske Semiotics Analysis In The Theme Of Gender Equality In The Film “Mulan” (International Journal of Cultural and Social Science, 2022)
Film is one of the mass communication media that displays a series of moving images with a storyline played by the actors who are produced to convey a message to the audience. For this reason, the message contained in the film becomes an important point for the community. One of the films that contains many messages in it is the film "Mulan" which is the result of the production of the largest animation company in the world, namely Walt Disney Pictures. This film raises the theme of gender equality as the main problem. The researcher then decided to explore the meaning of gender equality contained in the film. The theory used in this study is a theory using semiotic analysis by examining signs and how they work. This type of research is a descriptive study and uses the Jhon Fiske semiotics method. Data collection techniques in the form of observation, documentation, literature study, and using triangulation of theories and methods. The results of the analysis show that in this study there are representations of gender equality contained in the film "Disney Mulan" in the form of: access, participation, control, and benefits.